THE EFFECT OF ADDING CHESTNUT TANIN EXTRACTS ON RATION TO PERFORMANCE OF NEW ZEALAND WHITE RABBIT CROSSBREED - SINAGA, SAULAND; Rusmana, Denny; Apritama, Apritama; Nisa, Danela (Fakultas Peternakan, Universitas Padjadjaran, 2023)
Sauland Sinaga, Deni Rusmana, Apritama and Danela NisaABSTRACTThis study aims to determine the impact of adding chestnut tannin extract to the diet on developing body weight gain and ratio conversion of New Zealand White crossbreed rabbits. Experimental methods with a completely randomized design were used in this research. There were four treatments: R0 (Control Feed); R1 (0.25% addition of chestnut tannin extract); R2 (0.5% addition of chestnut tannin extract); R3 (0.75% addition of chestnut tannin extract); with five replications. Statistical analysis showed that the result was significant for body weight gain (p<0.05) and not for protein consumption and ratio, conversion and protein efficiency ratio, percentage, and component carcass. Tannin from a chestnut tree extract can be used at 0.25% in rabbit ration as an additive to replace antibiotics and growth promoters in rabbits.